Commensal Bacteria Augment Staphylococcus aureus septic Arthritis in a Dose-Dependent Manner - Fei, Ying; Ali, Abukar; Mohammad, Majd; Jin, Tao (Frontiers in Cellular and Infection Microbiology, 2022)
Background Septic arthritis is considered one of the most dangerous joints diseases and is mainly caused by the Gram-positive bacterium Staphylococcus aureus (S. aureus). Human skin commensals are known to augment S. aureus infections. The aim of this study was to investigate if human commensals could augment S. aureus-induced septic arthritis. Method NMRI mice were inoculated with S. aureus alone or with a mixture of S. aureus together with either of the human commensal Staphylococcus epidermidis (S. epidermidis) or Streptococcus mitis (S. mitis). The clinical, radiological and histopathological changes due to septic arthritis were observed. Furthermore, the serum levels of chemokines and cytokines were assessed. Results Mice inoculated with a mixture of S. aureus and S. epidermidis or S. mitis developed more severe and frequent clinical arthritis compared to mice inoculated with S. aureus alone. This finding was verified pathologically and radiologically. Furthermore, the ability of mice to clear invading bacteria in the joints but not in kidneys was hampered by the bacterial mixture compared to S. aureus alone. Serum levels of monocyte chemoattractant protein 1 were elevated at the early phase of disease in the mice infected with bacterial mixture compared with ones infected with S. aureus alone. Finally, the augmentation effect in septic arthritis development by S. epidermidis was bacterial dose-dependent. Conclusion The commensal bacteria dose-dependently augment S. aureus-induced septic arthritis in a mouse model of septic arthritis.